KAJIAN Psikolinguistik pa da Ta taran Sintaksis DALAM Basantara Belanda-Indonesia - Riyanto, Sugeng (LITERA, 2013)
This study discusses the Dutch-Indonesian interlanguage using psycholinguistics in the syntactic level. The sentences in the interlanguage are expressed by thirty students with different language proficiency levels and are analyzed to test the prediction of Pienemann’s processability theory (2005a, 2005b, 2005c, dan 2007). This study proves the validity of the processability theory. The Dutch learners mastering sentences with the most difficult level of processability also master sentences with easier levels of processability. The results from the learners with the high proficiency support the processability theory more firmly than those from the learners with the lower proficiency. Learners rely on meaning when they are not sure of their grammatical competence. Interlanguage is formed because of the demand on the learners that in a short time they have to express concepts and ideas in their minds but the facilitating divices are still limited, while they have already mastered the first language and possibly other languages.